ОРГАНІЗАЦІЙНО-ПРАВОВІ ФОРМИ ПІДПРИЄМНИЦЬКИХ ТОВАРИСТВ У КРАЇНАХ МАГРИБУ (АЛЖИР, МАРОККО, ТУНІС) - Сегеда, Іван Сергійович (SUPREMANCE OF LAW, 2019)
The article deals with the legislation of Algeria, Morocco and Tunisia, which regulates legal forms of commercial companies, in comparison with the Ukrainian legislation. The author characterized different legal forms of commercial companies, identifi ed their main common and distinctive peculiarities, as well as the most popular forms of commercial companies in the region. The author formulated some recommendations on optimal legal forms of entrepreneurship for expanding the Ukrainian business to markets of the Maghreb states.